K-MEANS ALGORITHM TO DETERMINE MARKETING STRATEGY AT CODEVERSE COMPUTER ACCESSORIES STORE - Burhanuddin Balit, Muhamad Naufal; Utomo, Fandy Setyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Artificial Intelligence (AI) is currently gaining popularity across various industries, including healthcare, finance, and others. In this study, AI technology is employed to devise an optimal marketing strategy for Code Verse Computer Accessories Store using the K-Means algorithm. As part of machine learning, the K-Means algorithm, categorized under unsupervised learning, is implemented to cluster sales data for computer accessory products over the last three months of 2023. The results of the K-Means analysis identify two main clusters. Cluster one (Cluster 1) comprises products such as Mouse, Keyboard, Monitor, Headset, and Speaker, indicating consistent purchasing patterns and high consumer interest. Recommendations are made to increase stock for Cluster 1. Meanwhile, Cluster two (Cluster 2) consists of Mic products with lower interest, and it is not advisable to increase stock. The implementation of K-Means provides insights into purchasing patterns, enabling Code Verse to develop more effective marketing and inventory management strategies. Keywords: K-Means algorithm; artificial intelligence; clustering Abstract: Kecerdasan Buatan (AI) kini meraih popularitas dalam berbagai industri, termasuk sektor kesehatan, keuangan, dan lainnya. Pada penelitian ini, teknologi AI digunakan untuk merancang strategi pemasaran optimal bagi Toko Aksesoris Komputer CodeVerse dengan menggunakan Algoritma K-Means. Sebagai bagian dari machine learning, Algoritma K-Means, yang termasuk dalam kategori unsupervised learning, diimplementasikan untuk mengelompokkan data penjualan produk selama tiga bulan terakhir tahun 2023. Hasil dari analisis K-Means mengidentifikasi dua cluster utama. Cluster pertama (Cluster 1) terdiri dari produk Mouse, Keyboard, Monitor, Headset, dan Speaker, menunjukkan pola pembelian yang konsisten dan tingginya minat konsumen. Rekomendasi untuk menambah stok diberikan. Sementara itu, Cluster kedua (Cluster 2) terdiri dari produk Mic dengan minat lebih rendah, dan tidak disarankan untuk menambah stok. Implementasi K-Means memberikan wawasan tentang pola pembelian, memungkinkan CodeVerse mengembangkan strategi pemasaran dan manajemen persediaan yang lebih efektif. Keywords: Algoritma k-means; kecerdasan buatan; clustering